2017
DOI: 10.1073/pnas.1701631114
|View full text |Cite
|
Sign up to set email alerts
|

Inducible CTCF insulator delays the IgH 3′ regulatory region-mediated activation of germline promoters and alters class switching

Abstract: Class switch recombination (CSR) plays an important role in adaptive immune response by enabling mature B cells to switch from IgM expression to the expression of downstream isotypes. CSR is preceded by inducible germline (GL) transcription of the constant genes and is controlled by the 3′ regulatory region (3′RR) in a stimulus-dependent manner. Why the 3′RR-mediated upregulation of GL transcription is delayed to the mature B-cell stage is presently unknown. Here we show that mice devoid of an inducible CTCF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 36 publications
5
54
0
Order By: Relevance
“…Purified resting or LPS-activated splenic B cells were singlecell-sorted and assayed for monoallelic transcription of Sγ3 and Sγ2b, as described above. Interestingly, and in agreement with the high levels of Sγ3 transcripts detected in resting B cell populations (15), already at 0 h, over 40% of alleles expressed Sγ3, while only 6.5% transcribed Sγ2b and 4% coexpressed Sγ3 and Sγ2b (Fig. 3 B-D).…”
Section: Iγ3 Cγ3supporting
confidence: 87%
See 4 more Smart Citations
“…Purified resting or LPS-activated splenic B cells were singlecell-sorted and assayed for monoallelic transcription of Sγ3 and Sγ2b, as described above. Interestingly, and in agreement with the high levels of Sγ3 transcripts detected in resting B cell populations (15), already at 0 h, over 40% of alleles expressed Sγ3, while only 6.5% transcribed Sγ2b and 4% coexpressed Sγ3 and Sγ2b (Fig. 3 B-D).…”
Section: Iγ3 Cγ3supporting
confidence: 87%
“…To test this, we used a mouse genetic setting that magnifies initial monoallelic activation of the Iγ3 promoter. We have recently shown that deletion of the inducible insulator 5′hs1RI in Cα leads to premature activation of the Iγ3 and Iγ2b promoters (15). In resting (nonactivated) 5′hs1RI Δ/Δ splenic B cells, Sγ3 and Sγ2b transcript levels are unusually high compared with WT counterparts, with Sγ3 transcripts displaying the biggest difference…”
Section: Activation Of Iγ3 Promoter Does Not Preclude Activation Of Iγ2bmentioning
confidence: 99%
See 3 more Smart Citations